Contribution to the comparison of conventional concentric magnetic gear and double stage concentric magnetic gear for high power offshore wind applications - Philippe, d’Almeida Renaud; Gilles, Agbokpanzo Richard; Macaire, Agbomahena Bienvenu (Institute of Advanced Engineering and Science, 2024)
Nowadays, the replacement of mechanical technologies by magnetic technologies has several advantages. Therefore, in this paper, we compare in an indirect drive chain the conventional concentric magnetic gear (CCMG) and the double-stage concentric magnetic gear (DSCMG) used as a speed multiplier for a high-power offshore wind turbine. This comparison is performed for the same gear ratio and the same torque at the input of both magnetic gears to obtain the same torque values at the output of each gear. The goal is to determine which one has the smaller amount of magnet and the higher volumetric torque density. After the calculation of the gear ratio, a first choice of geometrical parameters is adopted. Several simulations carried out by the finite element method (FEM) allowed to obtain the desired torques and to fix the final geometrical parameters of each magnetic gear. The results obtained show that the DSCMG has both the smallest magnet volume and the highest volumetric torque density compared to the CCMG.